Performance- and stimulus-dependent oscillations in monkey prefrontal cortex during short-term memory - Pipa, Gordon; Staedtler, Ellen S.; Rodriguez, Eugenio F.; Waltz, James A.; Muckli, Lars; Singer, Wolf; Goebel, Rainer; Munk, Matthias H. (Frontiers in Integrative Neuroscience, 2009)
Short-term memory requires the coordination of sub-processes like encoding, retention, retrieval and comparison of stored material to subsequent input. Neuronal oscillations have an inherent time structure, can effectively coordinate synaptic integration of large neuron populations and could therefore organize and integrate distributed sub-processes in time and space. We observed field potential oscillations (14–95 Hz) in ventral prefrontal cortex of monkeys performing a visual memory task. Stimulus-selective and performance-dependent oscillations occurred simultaneously at 65–95 Hz and 14–50 Hz, the latter being phase-locked throughout memory maintenance. We propose that prefrontal oscillatory activity may be instrumental for the dynamical integration of local and global neuronal processes underlying short-term memory.